Research ethics systems, processes, and awareness across Europe: Radiography research ethics standards for Europe (RRESFE). Issue 4 (November 2022) - Bockhold, S.; McNulty, J.; Abdurakman, E.; Bezzina, P.; Drey, N.; England, A.; Flinton, D.; Khine, R.; McEntee, M.; Mekiš, N.; Precht, H.; Rainford, L.; et al.
Abstract: Introduction: The Radiography Research Ethics Standards for Europe (RRESFE) project aims to provide a cross-sectional snapshot of current research ethics systems, processes, and awareness of such, across Europe together with identifying the associated challenges, education, and training needs. Methods: A cross-sectional online survey targeting radiography researchers in Europe was conducted. Data collection took place between April 26 and July 12, 2021, using a snowball sampling approach. Descriptive and analytical statistics were used to identify trends in research ethics frameworks across Europe. Results: 285 responses were received across 33 European and 23 non-European countries. Most (n = 221; 95%) European respondents stated ethics approval is required before commencing research in their country. Requirements around research ethics approval and awareness of such requirements varied by European region (X 2 (2, n = 129) = 7.234, p = 0.013) and were found to differ depending on the type of research participant and study design. Additionally, European respondents reported ethics approval is a national requirement more often than their non-European counterparts (X 2 (1, n = 282) = 4.316, p = 0.049). Requirements for ethics approval were also associated with the undergraduate programme duration (2-year vs. 3-year vs. 3.5 year vs. 4-year vs. multiple programme durations; X 2 (4, n = 231) = 10.075, p = 0.016) and availability of postgraduate training (postgraduate training available vs. postgraduate training not available; X 2 (1, n = 231) = 15.448, p = <0.001) within respondents' country. Conclusion: Respondents from countries with longer programme durations/availability of multiple programme lengths, availability of postgraduate training, and establishment of European Qualifications Framework Level 6 were generally associated with less uncertainty and more comprehensive research ethics requirements. Implications for practice: Results are informative of the current status of research ethics within evidence-based radiography.